If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-2x) = (-88) Remove parenthesis around (-2x) -1 * -2x = (-88) Multiply -1 * -2 2x = (-88) 2x = -88 Solving 2x = -88 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = -44 Simplifying x = -44
| 2(x+4)=5x-1 | | 6p+12=4p | | -4x+12=x+17 | | 12-9x=52-16x | | 3x-7=-4x | | 3x-7=-1 | | -x-6=-2 | | (x^2-9)(x+4)=0 | | 18+x=-2 | | X^4+6x=0 | | 5x-7=103 | | (x^2-2)(x^2+3)=0 | | 170-5x=6x+5 | | 5x+1=3x+13 | | -4x^2-4x+3=0 | | 6p+3=3p+12 | | q=4.5-0.5 | | P^2-6p+8= | | 5x-2=x-14 | | 58-5=8+19 | | 2(x-12)=3(x-8) | | -9x^2=100 | | 6x^2+486=0 | | 15+3x=-3 | | y+2=5y+18 | | y=-0.125+1.375+1.5 | | 108-5x=31x+20 | | 6h+5=4h-17 | | 2w-2x-y+7w+15x-5y= | | 124-3x=6x+16 | | 11x-3y+13w+3y-4w+2x= | | 6w+9y+5x+8x-15y+4w= |